2015
DOI: 10.1016/j.jfda.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and solubility of selected trace metals in leaf and bagged black teas commercialized in Poland

Abstract: The objective of this study was to determine the concentrations of heavy metals in bagged and leaf black teas of the same brand and evaluate the percentage transfer of metals to tea infusion to assess the consumer exposure. Ten leaf black teas and 10 bagged black teas of the same brand available in Poland were analyzed for Zn, Mn, Cd, Pb, Ni, Co, Cr, Al, and Fe concentrations both in dry material and their infusion. The bagged teas contained higher amounts of Pb, Mn, Fe, Ni, Al, and Cr compared with leaf teas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
7
27
0
Order By: Relevance
“…They followed the order Mn > Zn > Fe > Cu. The quantities of metallic elements assayed in the study are in agreement with the values found in other research on tea, erva-mate, or medicinal herb infusions (Pozebon et al 2015;Polechonska et al 2015;Salahinejad and Aflaki 2010;Konieczynski et al 2015Konieczynski et al , 2016. However, the level of Zn and Cu is higher in all erva-mate samples than that determined in black and green teas, as confirmed by post hoc Tukey's test.…”
Section: Essential Elementssupporting
confidence: 90%
“…They followed the order Mn > Zn > Fe > Cu. The quantities of metallic elements assayed in the study are in agreement with the values found in other research on tea, erva-mate, or medicinal herb infusions (Pozebon et al 2015;Polechonska et al 2015;Salahinejad and Aflaki 2010;Konieczynski et al 2015Konieczynski et al , 2016. However, the level of Zn and Cu is higher in all erva-mate samples than that determined in black and green teas, as confirmed by post hoc Tukey's test.…”
Section: Essential Elementssupporting
confidence: 90%
“…Herbal beverages (teas and herbal teas) are used worldwide due to their nutritional values and for health benefits, since they usually are not biologically aggressive (Pytlakowska et al 2012). It is known that billions of cups are consumed worldwide (Polechońska et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that Mn and Cu appeared to be released more into the infusion than brew extracts was explained for Camellia sinensis in terms of their potential for chelation with tannins and tannic acid which exudes on boiling (brew) such that when chelates precipitate, element content decreases [35]. In separate studies, little or no Pb was detected in leaves, made tea, and infusions from Camellia sinensis , common tea [32, 35, 36]. Camellia sinensis has been shown to release high concentrations of Mn in made tea and its infusions [28, 30, 36].…”
Section: Resultsmentioning
confidence: 99%